EFEKTIFITAS INSTAGRAM DALAM MEMPROMOSIKAN PENJUALAN KAMAR BATIQA HOTEL PEKANBARU - Ulfa, Maria; ", Musadad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
One of the factors supporting marketing is promotion. Along with developing technology, the promotion media is increasingly diverse from day to day one of them is through the internet media. In this research the internet media used is social media instagram.The purpose of this study is the influence of creative advertising of its effectiveness as a media promotion of sales through social media instagram.the population that is determined is all followers account @batiqahotels which amounted 1385 people, who then using the technique of sampling simple random sampling and 93 respondents obtained the respondents. The type of data used is primary data, obtained through questionnaires and interviews.The analytical tool used is a method of measuring the effectiveness of AIDA(attention, interest, desire and action) based on Paulus theory.The results of this study is there is a positive influence between attention (X1), interest (X2), desire (X3) and action (X4) on the responses of respondents that led to the effectiveness of instagram as a media campaign. This can be interpreted that if attention (X1), interest (X2), desire (X3) and action (X4) increases then the more effective instagram as a media campaign. Otherwise if decreased then the effectiveness of instagram as media campaign also decreased.Keyword: Promotion, Instagram, Efecctiveness